ДОСЛІДЖЕННЯ ФОРМ КРИВИХ ПЕРЕХІДНОГО ПРОЦЕСУ ПРИ КОМУТАЦІЯХ - Лободзинський , В.Ю. (Інститут електродинаміки Національної академії наук України, 2017)
It was conducted theoretical research and analysis of overvoltages transient phenomenon in switching transients of high-voltage cable line. Theoretical research has revealed the basic laws of overvoltages at the typical switching.  The analysis of transient process components allows to analyze the shape of the transient-response curve for determination of duration, the amplitude of the forced and free components of  switching overvoltages, which have effects on insulation of high-voltage cable line. It was defined that the maximum voltage is mainly determined by the switching angle and  self-resonant frequency  which determine the amplitude of the transient (free) component. References 7, figures 5.